An Arithmetic-Trigonometric Optimization Algorithm with Application for Control of Real-Time Pressure Process Plant - Devan, P.A.M. (MDPI, 2022)
This paper proposes a novel hybrid arithmeticâtrigonometric optimization algorithm (ATOA) using different trigonometric functions for complex and continuously evolving real-time problems. The proposed algorithm adopts different trigonometric functions, namely sin, cos, and tan, with the conventional sine cosine algorithm (SCA) and arithmetic optimization algorithm (AOA) to improve the convergence rate and optimal search area in the exploration and exploitation phases. The proposed algorithm is simulated with 33 distinct optimization test problems consisting of multiple dimensions to showcase the effectiveness of ATOA. Furthermore, the different variants of the ATOA optimization technique are used to obtain the controller parameters for the real-time pressure process plant to investigate its performance. The obtained results have shown a remarkable performance improvement compared with the existing algorithms. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.